2019
DOI: 10.1192/bjo.2019.61
|View full text |Cite
|
Sign up to set email alerts
|

Psychological screening of adults and young people following the Manchester Arena incident

Abstract: Background Terrorist attacks have increased globally since the late 1990s with clear evidence of psychological distress across both adults and children and young people (CYP). After the Manchester Arena terrorist attack, the Resilience Hub was established to identify people in need of psychological and psychosocial support. Aims To examine the severity of symptoms and impact of the programme. Method The hub offers outreach, screening, clinical telephone triage and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Following the Manchester Arena attack (2017), members of the archiving team met with clinical staff at the Manchester Resilience Hub (a service set up to support people with mental health-related problems following the arena incident; French et al, 2019). Group meetings offered staff guidance and support on how to process their emotions and look after their well-being during the archiving process.…”
Section: Practice Implications For Professionalsmentioning
confidence: 99%
“…Following the Manchester Arena attack (2017), members of the archiving team met with clinical staff at the Manchester Resilience Hub (a service set up to support people with mental health-related problems following the arena incident; French et al, 2019). Group meetings offered staff guidance and support on how to process their emotions and look after their well-being during the archiving process.…”
Section: Practice Implications For Professionalsmentioning
confidence: 99%
“…A clinical outcomes evaluation is presented elsewhere [ 50 ]. The objectives of this process evaluation were: A logic model describing the resources and planning actions, necessary to implement parts of the seven-step model; A process evaluation relating procedures [ 51 ] and context [ 52 ] to programmatic outcomes (numbers screened and in receipt of support); An evaluation of how well Hub practices were embedded and sustained, using Normalisation Process Theory (NPT) [ 53 , 54 ], a sociological theory of the middle range [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of those programmes have concluded that screen-and-treat approaches may be a clinically effective approach for addressing mental health needs following major incidents (Brewin et al, 2010a;Cyhlarova, Knapp, & Mays, 2019;French et al, 2019;Gobin et al, 2018;Kerslake Report, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this are well-understood: a combination of low priority at strategic planning and policy development level, general low levels of public understanding, poor recognition in primary care, and the avoidance that is one of the defining symptoms. In recent years, health systems have begun to address this problem by instituting proactive outreach to affected populations, often coupled with screening and signposting into evidence-based treatments (Brewin et al, 2008; Dyb et al, 2014; French et al, 2019; Maslow et al, 2015). In this paper we report the first systematic attempt to assess the cost-effectiveness of this approach.…”
Section: Introductionmentioning
confidence: 99%